'I pastori non si arrestano!': Herding and its spatial agency in the Sardinian penal colonies - Puddu, Sabrina (Criminological encounters, 2022)
This essay attempts a reflection on rurality and herding by looking at a particular carceral setting: the Sardinian penal colony as established in the 19th c. and still surviving as a marginal institution within the national penal system. Despite the long-lasting effort to modernise and stabilise animal-farming and to eradicate herding as an allegedly criminogenic practice - effort to which penal colonies actively contributed both by dispossessing land used by the herders and by means of exemplarity as a model sedentary farm - errant herding has lingered in free society and also, in an apparent paradox, within the very carceral estates of the penal colony. I will discusshow, within the territorial project of the Sardinian penal colonies and its uncertain, yet extensive, structures of control and production, herding and the wondering of the herder after goats, sheep, and cattle in search for pastures and waters, is to a certain extent a creative practice whose spatial agency simultaneously challenges and is challenged by the spatial and institutional principles ofthe prison estate. This essay is grounded on archival and field research in the penal colonies of Mamone, Isili, and Is Arenas and makes use of drawings and photographs as key research tools.